Interdisciplinary Approach in Islamic Education - Khoirudin Miftah; Cindy Fatikasari Ibrahim; Opik Taupik Kurahman; Dadan Rusmana (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
This research explains the interdisciplinary approach in the study of Islamic education, recognizing its approach in Islamic education, as well as its benefits, and also the important points of this interdisciplinary approach in Islamic education.  The research method used is using library sources. This approach includes the search for library materials or secondary data, including primary materials such as books, journals, and sources relevant to the object under study. In Islamic education, the interdisciplinary approach plays an important role in improving the quality of education that is more comprehensive and relevant to the problems faced by the world today. In addition, the interdisciplinary approach provides learners with the foundation to build new solutions to various modern problems faced by Muslims, both domestically and around the world. To achieve greater success, the application of the interdisciplinary approach in Islamic education must be supported by adjustments to the curriculum that harmonize religious and general sciences and the provision of competent human resources in various scientific fields.